Hubungan Suhu, Kelembaban, Pencahayaan,Dan Pengelolaan Sampah Dengan Tingkat Kepadatan Lalat Di Pasar Oeba Kecamatan Kota Lama Kota Kupang - Olviana Reni Ina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Fly house is wrong one vector disease on human . one _ disease caused _ by vector this that is diarrhea . Diarrhea is state defecate _ _ more than 3 times in period time one day . Where vector fly fly to various dirty place _ and carry pathogens from the place the and spread to food and drink . Fly also no could breed without existence factor supportive environment _ breeding vector the like temperature , humidity and lighting . On 2020 market _ oeba is wrong one the place highest with density flies on average 10 tails / 30 seconds block grill . Destination study this is knowing connection temperature , humidity , lighting and management rubbish with density flies in the market Oeba Kota Lama District, Kupang City . Type study this is study survey analytic approach design cross sectional with To do observation direct and measurement for knowing connection temperature , humidity , lighting and management trash . Study this done in the market Oeba Old Town District kupang with sample as many as 82 places sales . Analysis of the data used analysis univariate and bivariate with test chi-square . Results study to density fly tall is 75.6 % . Results analysis statistical test shows that there is related variables _ with density fly that is humidity ( p= 0.036), lighting ( p = 0.007), management waste ( p = 0.000) and variable that is not there is connection that is temperature environment ( p = 0.224). For that need conducted work same Among government and Public local good merchant , manager market and Service Regency for notice cleanliness environment market .